Analisis Kohesi Leksikal dan Gramatikal Serta Koherensi dalam Teks Diskusi - Akhmad Ubedi; Dendy Sugono; Nurdin Nurdin (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2023)
Writing discussion text is a skill that must be mastered by junior high school students. However, in writing discussion texts the connectedness and linkage of sentences has not received serious attention, especially the use of lexical and grammatical cohesion and coherence. In this regard, the purpose of this study was to find out the inappropriate use of lexical and grammatical cohesion and coherence in the discussion texts of SMP Negeri Jakarta Timur students. This research deals with the object of study of the discussion texts of class IX students of State Middle School in East Jakarta as many as 602 texts. By random sampling, 64 discussion texts were selected and 585 sentences were collected. This is done by analyzing each sentence in the discussion text regarding the inappropriate use of lexical and grammatical cohesion and its coherence. Data were analyzed using a qualitative description method. The instrument used in this study is the human instrument. The results of this study indicate that the use of markers of lexical and grammatical cohesion and coherence is incorrect in 112 sentences or 19.15%. The use of lexical cohesion markers includes the use of repetition of 9 sentences or 1.53%, synonyms of 2 or 0.34%, antonyms of 1 sentence or 0.17%, and collocation of 2 sentences or 0.34%. The use of grammatical cohesion markers includes the use of references in 21 sentences or 3.59%, ellipsis 10 sentences or 1.71%, and conjunctions 33 sentences or 5.64%. The use of coherence markers includes the use of causal relations 6 sentences or 1.03%, affirmative relations 2 sentences or 0.34%, summation relations 5 sentences or 0.85%, conditional relations 2 sentences or 0.34%, relations purpose-conditions 2 sentences or 0.34%, contradictory relations 2 sentences or 0.34%, overgeneralization 2 sentences or 0.34%, and paraphrase relations 10 sentences .or 1.71%. Keywords: Lexical Cohesion, Grammatical Cohesion, Coherence, Discussion Textsi